Letter - Haldane, Charlotte Franken, 1894-1969
034-0109-001 INTERNATIONAL BRIGADE Dependants and Wounded Aid Committee Patrons: Harry Adams The Duchess of Atholl, MP. H.N. Brailsford Seymour Cocks, MP Ebby Edwards Prof. J.B.S. Haldane. F.R.S. Oliver Harris Will Lawther Sir Walter Layton Earl of Listowel Sir Peter Chalmers Mitchell, C.B.E.. F.R.S., F.Z.S.. D.Sc LL.D. J.B. Priestley Eleanor Rathbone, M.P. Ald. J. Reeves E. Shinwell, M.P. W.J.R. Squance G.R. Strauss, M.P. Wilfrid Roberts, M.P. Ellen Wilkinson. M.P. Hon Secretary: CHARLOTTE HALDANE Telephone: Temple Bar 0178 1 LITCHFIELD STREET, LONDON, W.C.2. December 16th, 1938. Mr. Tewson, Trade Union Congress, Transport House, S.W.1. Dear Mr. Tewson, We are holding a National Memorial Meeting in the Empress Stadium on January 8th. This meeting, which is above party or creed will be an opportunity for all democratic and progressive people to pay honour and tribute to those Britishers who fell in Spain. For the programme that we are producing on this occasion, we are anxious to have messages of support from representative leaders of progressive thought. May we ask you, therefore, if you would kindly send us a message suitable for printing in our programme on this occasion. Yours sincerely, Charlotte Haldane (Hon. Secretary) pp. 292/946/34/109